2017
DOI: 10.1108/qae-03-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Internal quality assurance systems: “tailor made” or “one size fits all” implementation?

Abstract: Purpose This paper aims to look at the characteristics of internal quality assurance (IQA) systems of higher education institutions to understand whether these systems tend to reproduce a given model, externally defined and suggested to institutions, or rather to be shaped by institutions’ features and interests. Design/methodology/approach The study is supported in the analysis of the content of self-assessment reports of 12 internal QA systems certified, in Portugal, between 2012 and 2015. An analysis grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
(44 reference statements)
1
20
0
2
Order By: Relevance
“…Based on the research results, if the school management wants to increase student satisfaction and loyalty, they must focus on the quality of the products and services they provide and the image of the school from the student's point of view. This research conducted by Temizer strengthens the writing of Cardoso et al (2017) which states that many internal performance measurements focus on standards originating from Europe. This European standard tends to be generalized in its use to measure the achievement of quality management performance in higher education institutions.…”
Section: Internal Satisfactionsupporting
confidence: 68%
See 1 more Smart Citation
“…Based on the research results, if the school management wants to increase student satisfaction and loyalty, they must focus on the quality of the products and services they provide and the image of the school from the student's point of view. This research conducted by Temizer strengthens the writing of Cardoso et al (2017) which states that many internal performance measurements focus on standards originating from Europe. This European standard tends to be generalized in its use to measure the achievement of quality management performance in higher education institutions.…”
Section: Internal Satisfactionsupporting
confidence: 68%
“…Public and private higher education institutions can do this in the same way. Cardo so et al (2017) found that higher education institutions need to find an internal assessment model that suits itself [22]. Most of the higher education institutions simply take without modifying the variables and selfassessment indicators of the quality management system that exists in Europe [22].…”
Section: Quality Assurance In Indonesian Universitiesmentioning
confidence: 99%
“…As a result, the internal systems of Portuguese institutions generally make reference to all these processes. However, they tend to be highly focused on teaching and learning (CARDOSO et al, 2017), which is evident in the fact that quality assurance processes and mechanisms are mainly oriented towards learning and teaching, while information management systems generally include data about the pedagogic performance of study programmes. The study carried out by Cardoso et al (2017) focused on a limited number of self-assessment reports which had been, at that time, submitted to A3ES for the certification of internal quality assurance systems.…”
Section: The Quality Assurance Of Third Mission Activitiesmentioning
confidence: 99%
“…However, they tend to be highly focused on teaching and learning (CARDOSO et al, 2017), which is evident in the fact that quality assurance processes and mechanisms are mainly oriented towards learning and teaching, while information management systems generally include data about the pedagogic performance of study programmes. The study carried out by Cardoso et al (2017) focused on a limited number of self-assessment reports which had been, at that time, submitted to A3ES for the certification of internal quality assurance systems. This study aims to extend the coverage to comprise all Portuguese universities, public or private, independent of whether their internal quality assurance systems have been certified by A3ES or not.…”
Section: The Quality Assurance Of Third Mission Activitiesmentioning
confidence: 99%
See 1 more Smart Citation